2007
DOI: 10.1111/j.1750-3841.2007.00564.x
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Drivers for Consumer Acceptance and Purchase Intent of Corn Tortilla

Abstract: The traditional production of corn tortilla has been modified by new processing technologies to make possible a commercial-scale production; this practice has resulted in products having sensory properties different from those produced by the traditional method. There is no published information on sensory attributes driving acceptance and purchase intent of corn tortillas. Identifying sensory drivers for acceptance and purchase intent of corn tortillas will help commercially produce products that satisfy cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 11 publications
2
34
0
Order By: Relevance
“…The majority of the variables were important predictors; however, ease of care and fabric were insignificant influencers on two of the garments. The results of this study confirmed previous studies that different criteria influenced consumers' purchase intentions and their overall acceptance of fashion products [12,13]; Eckman et al [39]; [14,16]; Herrata-Corredor et al [15]. This result is consistent with previous research that fashion/style and appearance were the most important attributes to young consumers and women when making a purchase decision [43]; North et al [46].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The majority of the variables were important predictors; however, ease of care and fabric were insignificant influencers on two of the garments. The results of this study confirmed previous studies that different criteria influenced consumers' purchase intentions and their overall acceptance of fashion products [12,13]; Eckman et al [39]; [14,16]; Herrata-Corredor et al [15]. This result is consistent with previous research that fashion/style and appearance were the most important attributes to young consumers and women when making a purchase decision [43]; North et al [46].…”
Section: Discussionsupporting
confidence: 83%
“…Research has investigated the influence of clothing attributes on consumers' purchase intentions and found that consumers are significantly influenced by different attributes when determining overall acceptance of fashion products [12][13][14][15][16]. In the case of fashion items, an additional consideration is fashion leadership which influences product evaluation and purchasing of products [7,[17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…These are the variables that best explain acceptance of this beverage, alone accounting for 41.34% of the variance. In accordance with the antecedents established in the formulation of H3 and as established elsewhere (Ronteltap et al, 2007;Herrera et al, 2007;Sae-Eaw et al, 2007;Chung et al, 2011;Montouto et al, 2012;Talsma et al, 2013;Espina et al, 2014), it is proposed that efforts focus on new visual, olfactory and taste-related sensations with a view to producing an appetising product that offers good value for money. Research and development institutes such as the INIA should innovate towards products that highlight these sensations.…”
Section: Discussionmentioning
confidence: 99%
“…Frewer et al, 1997;Ronteltap et al, 2007;Vanhonacker et al, 2013), and sensory attributes (e.g. Elsner et al, 1998;Herrera et al, 2007;Sae-Eaw et al, 2007;Chung et al, 2011;Montouto et al, 2012;Talsma et al, 2013;Espina et al, 2014;Bearth et al, 2014) influence the intention to consume: H1: The expected health benefits of the new natural sparkling red wine positively affect the intention to consume it.…”
Section: Introductionmentioning
confidence: 99%
“…Many aspects of the tortilla production still depend on the operator's expertise such as well as dough input, mixing, shaping, baking and others process parameters. Herrera-Corredor et al (2007) concluded in a consumer study that overall acceptance of corn tortillas depended on chewiness as well as overall liking. Purchase intent was influenced mainly by appearance, plasticity, chewiness, taste, and overall liking.…”
Section: Introductionmentioning
confidence: 97%